Thyroid-Stimulating Hormone Stimulation Tests in the Bottlenose Dolphin (Tursiops truncatus) - Dorian S. Houser; Cory Champagne; Daniel E. Crocker (Journal of Zoological and Botanical Gardens, 2021)
Stimulation of the thyroid with thyroid-stimulating hormone (TSH) is a potentially useful diagnostic of thyroid dysfunction, but little is known about the response of the thyroid to TSH stimulation in bottlenose dolphins (Tursiops truncatus). To better characterize the response of the dolphin thyroid to TSH stimulation, five adult dolphins participated in a TSH stimulation study. Dolphins voluntarily beached onto a padded mat and were given a 1.5 mg intramuscular injection of human recombinant TSH. Blood samples collected the day prior, at multiple intervals the day of, and daily for three days after the injection were analyzed via radioimmunoassay for free and total triiodothyronine (fT3 and tT3), and free and total thyroxine (fT4 and tT4). Significant increases in circulating fT3, fT4, and tT4 were observed with peaks occurring for all hormones the day after the TSH injection; maximal increases were 44%, 47%, and 23% for each hormone, respectively. Temporal patterns in the hormones potentially reflected feedback mechanisms countering the surge in fT3 following stimulation. Though recombinant human TSH was effective at stimulating hormone release, it is likely that use of dolphin or dolphin-derived TSH would enhance the clinical utility of the stimulation test, as would the development of antibodies specific to dolphin TSH.